Analisa Pembangkit Listrik Tenaga Uap Skala Laboratorium Dengan Bahan Bakar LPG - Jatmiko Edi Siswanto (Journal of Electrical Power Control and Automation (JEPCA), 2021)
The steam turbine is an initial drive that converts the potential energy of steam into kinetic energy and is subsequently converted into mechanical energy in the form of a turbine shaft rotation, directly or with the help of a reduction gear, connected to the mechanism to be driven. In research to analyze the performance of a steam turbine using LPG gas as fuel. Where in this study using the results of wet steam to move the turbine shaft with variations in pressure (7Bar, 6Bar, 5Bar and 4Bar). So that the maximum result is 7 Bar, the steam mass obtained is 0.09 with a time of 1.5 hours by heating 15 liters of water, the steam power produced is 25.6 Watts, the shaft power is 18.01 Watts and the maximum electrical power produced is 20 Watts. the turbine work efficiency is 78.12% and the result is a generator efficiency of 25%.